TABAYYUN AS A CRUCIAL ASPECT IN THE QURANIC CONCEPT OF UMMAH ANALYSIS OF â€œTABAYYUNâ€ IN SURA AL-HUJURAAT (49:6) - Azzuhri, Anggi (State Institute of Islamic Studies (IAIN) Palu, 2020)
Khairu Ummah appears in surah 3:110 associated to the society on which Prophet Muhammad lived. This term shows that there is a supreme concept of the highest level of civilization since the society of that period is considered as an excellent civilization. There are several requirements to fulfil in order to reach the status of khairu ummah, those are the promotion of virtue, prevention of vice, and Iman in Allah. However, those requirements are very general thus it is necessary to decipher specific aspect to reach one of them. In another surah, Al-Hujuraat (49), Allah detailly explains the major features of the Mu’minun (those who believe). Of the features is Tabayyun, appears in the sixth verse in the context of incoming information. Examining the semantic concept of Tabayyun is a step to reveal the specific aspect to gain the status of the ideal Ummah. This work is deciphering the concept of Tabayyun according to the Qur’an through two main approaches: Semantic analysis and Composition examination. These both methods are conducted by two distinguished contemporary scholars, Toshihiko Izutsu and Hamiduddin Al-Farahi, to find the philosophical meaning of a particular term from the Qur’an. Eventually, it is concluded that the Tabayyun definition is an important high-level social ethics that only true believer can perform it. The absence of Tabayyun leads not only to a wrong decision but to a major conflict in society even the disintegration of it.